2013
DOI: 10.1556/comec.14.2013.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal colonisation of roots of grass species differing in invasiveness

Abstract: Recent research indicates that the soil microbial community, particularly arbuscular mycorrhizal fungi (AMF), can influence plant invasion in several ways. We tested if 1) invasive species are colonised by AMF to a lower degree than resident native species, and 2) AMF colonisation of native plants is lower in a community inhabited by an invasive species than in an uninvaded resident community. The two tests were run in semiarid temperate grasslands on grass (Poaceae) species, and the frequency and intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
2
9
1
3
Order By: Relevance
“…Similarly, C. epigejos showed poor mycorrhizal colonization on coal mine spoil banks and moderate growth response to mycorrhizal infection in a pot experiment (Rydlová and Vosátka, 2001). Our earlier field study (Endresz et al, 2013) also suggested that the invasive Calamagrostis and Cynodon are not dependent on AMF symbionts, while the non-invasive Chrysopogon is (Danthonia was not examined then). In a semiarid steppe, Calamagrostis and Cynodon consistently displayed a lower degree of AMF colonization than resident grasses, including Chrysopogon, and the native bunchgrasses Festuca vaginata and Stipa borysthenica attained lower degree of AMF infection in stands invaded by Calamagrostis or Cynodon than in intact community (Endresz et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, C. epigejos showed poor mycorrhizal colonization on coal mine spoil banks and moderate growth response to mycorrhizal infection in a pot experiment (Rydlová and Vosátka, 2001). Our earlier field study (Endresz et al, 2013) also suggested that the invasive Calamagrostis and Cynodon are not dependent on AMF symbionts, while the non-invasive Chrysopogon is (Danthonia was not examined then). In a semiarid steppe, Calamagrostis and Cynodon consistently displayed a lower degree of AMF colonization than resident grasses, including Chrysopogon, and the native bunchgrasses Festuca vaginata and Stipa borysthenica attained lower degree of AMF infection in stands invaded by Calamagrostis or Cynodon than in intact community (Endresz et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Our earlier field study (Endresz et al, 2013) also suggested that the invasive Calamagrostis and Cynodon are not dependent on AMF symbionts, while the non-invasive Chrysopogon is (Danthonia was not examined then). In a semiarid steppe, Calamagrostis and Cynodon consistently displayed a lower degree of AMF colonization than resident grasses, including Chrysopogon, and the native bunchgrasses Festuca vaginata and Stipa borysthenica attained lower degree of AMF infection in stands invaded by Calamagrostis or Cynodon than in intact community (Endresz et al, 2013). Since in the same study we found Calamagrostis to have higher degree of AMF infection in nutrient poor sand grassland than in humus rich loess grassland, and others (Kovács and Szigetvári, 2002;Lingfei et al, 2005) reported intense AMF colonization for Cynodon, these two invasive species can be considered as facultative mycorrhizal plants.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is unclear how quickly these legacy effects occur or attenuate after an invasive plant is removed, as well as how soon the community may return to the structure and functioning of the previously native state [42]. In certain instances, after an invasive is removed, any changes in AMF abundance and diversity are fleeting, because differences in abundance and richness return rapidly with the return of the native vegetation type [14,38]. In contrast, in other studies [37] even a highly mycorrhizal invasive plant may not rapidly alter the AMF community, even after 29 weeks.…”
Section: Arbuscular and Ectomycorrhizal Fungimentioning
confidence: 99%
“…AMF communities affect plant communities in complex ways: like plants, not all AMF species play the same role in ecosystems (Hart et al 2003). The effects of AMF on plants are species-specific (Hoeksema et al 2010;Endresz et al 2013), but also depend on environmental conditions (Grime et al 1987;Hartnett and Wilson, 1999;Kytöviita et al 2003), and higher AMF root colonization is not always linked with better vegetation recovery (Richter et al 2002). Further research is required to explore how different ecosystem components can affect overall ecosystem recovery, and how they could be used to facilitate or to accelerate this recovery in a restoration context (Allen, 1989;Herrera et al 1993;Callaway et al 2001;Kardol et al 2009).…”
Section: Ecosystem Recoverymentioning
confidence: 99%